Preserving and perfusing the allograft pancreas: Past, present, and future - Dholakia, S; Royston, E; Sharples, E; Sankaran, V; Ploeg, R; Friend, P (Elsevier, 2018)
The concept of organ preservation by perfusion dates back to the mid-19th century. Innovations since then have included temperature regulation, perfusion fluid composition and various pumping systems. Advances made in liver, heart and kidney machine preservation are now contributing to increased graft utilisation, assessment of graft viability and potentially improved graft survival. Pancreas transplantation has not benefitted to the same extent from the application of perfusion technology, although the need is just as great. This overview reviews current pancreas specific preservation techniques. We explore concepts, which include static cold storage, use of preservation solutions, the ‘two-layer method’, and machine perfusion. We also discuss ideas for future development. Narrative review of literature from inception to December 2017 using OVID interfaces searching EMBASE, Google Scholar, and MEDLINE databases. All studies relevant to pancreas perfusion and preservation were examined for clinical relevance with no exclusion criteria. Conference papers and presentations were also reviewed and included where appropriate. The application of recent advances in understanding in ischaemia-reperfusion as well as technical developments in machine preservation Ischaemia-reperfusion have the potential to improve organ utilisation, viability and outcome.